2005
DOI: 10.1063/1.1898449
|View full text |Cite
|
Sign up to set email alerts
|

Microbridge testing of plasma-enhanced chemical-vapor deposited silicon oxide films on silicon wafers

Abstract: This is the Pre-Published Version 2 Plasma-enhanced chemical vapor deposited (PECVD) silane-based oxides (SiO x ) have been widely used in both microelectronics and MEMS (MicroElectroMechanical Systems) to form electrical and/or mechanical components. In this paper, a novel nanoindentation-based microbridge testing method is developed to measure both the residual stresses and Young's modulus of PECVD SiO x films on silicon wafers. Theoretically, we considered both the substrate deformation and residual stress … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…Previous study has suggested that the deformable boundary was an important factor that results in the difference. A complicated mechanism model to modify boundary conditions has been employed to circumvent this problem [33]. However, the mechanism model still required FEM to obtain required parameters to solve the deformable boundary condition.…”
Section: Effect Of M H and α On The Thermoelastic Responsementioning
confidence: 99%
“…Previous study has suggested that the deformable boundary was an important factor that results in the difference. A complicated mechanism model to modify boundary conditions has been employed to circumvent this problem [33]. However, the mechanism model still required FEM to obtain required parameters to solve the deformable boundary condition.…”
Section: Effect Of M H and α On The Thermoelastic Responsementioning
confidence: 99%
“…To evaluate the mechanical performance of the transparency, we have characterized the transparency cantilever beams with different thickness using nanoindentation measurement. The test was conducted on a TriboIndenter TM nanoindentation system (Hysitron Inc.) equipped with a 20 µm width wedge tip [15]. The cantilever beams were carefully aligned to be perpendicular to either the x-or y-axis of the nanoindenter stage.…”
Section: Nanoindentation Proceduresmentioning
confidence: 99%
“…In this section, we introduce a novel nanoindentation-based microbridge testing method, which has the advantage of being able to measure residual stress and Young's modulus of the thin film material simultaneously (Cao et al 2005). It is also easier to handle than uniaxile micro-tensile testing and avoids the problem of stress concentration of the bulge testing method (Cao et al 2005).…”
Section: Methodsmentioning
confidence: 99%
“…It is also easier to handle than uniaxile micro-tensile testing and avoids the problem of stress concentration of the bulge testing method (Cao et al 2005).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation